Harnessing Water for Greater Regional Good - Thanju, Jeewan Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
No abstract available DOI: http://dx.doi.org/10.3126/hn.v11i0.7153 Hydro Nepal Vol.11 2011 pp.5